Utilization of LED Grow Lights for Optical Wireless Communication-Based RF-Free Smart-Farming System - Sana Javed; Louey Issaoui; Seonghyeon Cho; Hyunchae Chun (Sensors, 2021)
Indoor smart-farming based on artificial grow lights has gained attention in the past few years. In modern agricultural technology, the growth status is generally monitored and controlled by radio-frequency communication networks. However, it is reported that the radio frequency (RF) could negatively impact the growth rate and the health condition of the vegetables. This work proposes an energy-efficient solution replacing or augmenting the current RF system by utilizing light-emitting diodes (LEDs) as the grow lights and adopting visible light communications and optical camera communication for the smart-farming systems. In particular, in the proposed system, communication data is modulated via a 24% additional green grow LED light that is also known to be beneficial for the growth of the vegetables. Optical cameras capture the modulated green light reflected from the vegetables for the uplink connection. A combination of white ceiling LEDs and photodetectors provides the downlink, enabling an RF-free communication network as a whole. In the proposed architecture, the smart-farming units are modularized, leading to flexible mobility. Following theoretical analysis and simulations, a proof-of-concept demonstration presents the feasibility of the proposed architecture by successfully demonstrating the maximum data rates of 840 b/s (uplink) and 20 Mb/s (downlink).